A survey on parent' attiudes towards their children's learning English at the primary school. M.A. Thesis Linguisitcs: 60 14 01 11 - Nguyễn, Thị Ngọc Anh (ĐHNN, 2017)
This study investigated the parents’ attitudes towards students’ English language (EL) learning at Hai Thanh Primary School (HTPS), Duong Kinh District, Hai Phong city. 450 parents of the HTPS students participated in the study. The data for the study was collected by these instruments: survey questionnaires and interviews with 22 parents.